Perancangan Sistem Monitoring Volume Air Dengan Sensor Ultrasonic HC-SR04 Menggunakan Mikrokontroler Arduino Uno: Perancangan Sistem Monitoring Volume Air Dengan Sensor Ultrasonic HC-SR04 Menggunakan Mikrokontroler Arduino Uno - Samosir, Theofilus Herly Hatonangan; Hidayat, Imam (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Water volume monitoring is an important aspect of water resource management to prevent wastage, water shortages, and flood risks. However, manual monitoring processes are still inefficient and prone to measurement errors. Therefore, this study aims to design and implement an automatic and real-time water volume detection system based on the Arduino Uno microcontroller. The system utilizes an HC-SR04 ultrasonic sensor to measure the distance between the sensor and the water surface, which is then converted into water level or volume information. The measurement results are displayed on a 16Ã—2 LCD and are complemented by LED indicators and a buzzer as an early warning system. A green LED indicates safe conditions, a yellow LED indicates warning conditions, and a red LED accompanied by a buzzer indicates dangerous conditions. The research method includes circuit design, programming using the Arduino IDE, as well as system testing and calibration. The test results show that the system is capable of detecting changes in water level with fairly good accuracy and providing appropriate responses based on predefined conditions. This system is considered effective, easy to implement, and relatively low-cost. Therefore, the application of Arduino Uno in a water volume detection system can serve as a practical solution for automatic water monitoring and has the potential to be further developed with Internet of Things (IoT)